Experience of N-acetylcysteine airway management in the successful treatment of one case of critical condition with COVID-19: A case report. Issue 42 (16th October 2020) - Liu, Yan; Wang, Meifang; Luo, Guoshi; Qian, Xin; Wu, Chenglin; Zhang, Yizhong; Chen, Biyu; Leung, Elaine Lai-Han; Tang, Yijun
Abstract: Rationale: The new coronavirus pneumonia Corona Virus Disease 2019 (COVID-19) has become a global pandemic. Patients with critically COVID-19 usually require invasive respiratory support, and the airway management is particularly important and the prognosis is poor. Patient concerns: A 64-year-old man with an anastomotic fistula after radical treatment of esophageal cancer and right-side encapsulated pyopneumothorax was admitted with cough and dyspnea. Diagnosis: The patient was diagnosed with novel coronavirus pneumonia and right-side encapsulated pyopneumothorax by pharyngeal swab nucleic acid test in combination with chest computed tomography (CT). Interventions: The patient was treated with antibiotics, antiviral and antibacterial medications, respiratory support, expectorant nebulization, and nutritional support. But he expressed progressive deterioration. Endotracheal intubation and mechanical ventilation were performed since the onset of the type - respiratory failure on the 13th day of admission. The patient had persistent refractory hypercapnia after mechanical ventilation. Based on the treatment mentioned above, combined with repeated bronchoalveolar lavage by using N-acetylcysteine (NAC) inhalation solution, the patients refractory hypercapnia was gradually improved. Outcomes: The patient was cured and discharged after being given the mechanical ventilation for 26 days as well as 46 days of hospitalization, currently is surviving well. Lessons: : Patients with severe conditions of novel coronavirus pneumonia often encounter bacterial infection in their later illness-stages. They may suffer respiratory failure and refractory hypercapnia that is difficult to improve due to excessive mucus secretion leading to small airway obstruction. This study provided a new insight on the proper treatment severe COVID-19 patients. The use of reasonable antibiotics and symptomatic respiratory support and other treatment, timely artificial airway and repeated bronchoalveolar NAC inhalation solution lavage, expectorant and other airway management are essential for such patients.